2007
DOI: 10.1185/030079907x187865
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of immunotherapy with SQ allergen extract for patients with seasonal allergic rhinoconjunctivitis in selected European countries

Abstract: The study shows that immunotherapy with SQ allergen extract is cost-effective in a wide range of national environments, and that cost-effectiveness differences by country are largely a result of different practices in the up-dosing phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…[209][210][211][212] Seven studies based on RCT data conducted from a health system perspective and using QALYS as their outcome measure suggests that SLIT and SCIT would be considered cost-effective in this patient population in United Kingdom at the standard National Institute for Health and Care Excellence (NICE) cost-effectiveness threshold of £20 000 (€24 616) per QALY. [213][214][215][216][217][218][219] The studies comparing SCIT and SLIT have given mixed results and do not allow us to conclude whether either treatment is more cost-effective. 220 ICERs for cost evaluations of AIT seem to vary substantially between different health systems suggesting that straightforward conclusions may not be generalizable even across seemingly similar countries.…”
Section: Pharmacoeconomic Aspe Cts Of Ait Versus Pharmacothe Rapy Fmentioning
confidence: 99%
See 1 more Smart Citation
“…[209][210][211][212] Seven studies based on RCT data conducted from a health system perspective and using QALYS as their outcome measure suggests that SLIT and SCIT would be considered cost-effective in this patient population in United Kingdom at the standard National Institute for Health and Care Excellence (NICE) cost-effectiveness threshold of £20 000 (€24 616) per QALY. [213][214][215][216][217][218][219] The studies comparing SCIT and SLIT have given mixed results and do not allow us to conclude whether either treatment is more cost-effective. 220 ICERs for cost evaluations of AIT seem to vary substantially between different health systems suggesting that straightforward conclusions may not be generalizable even across seemingly similar countries.…”
Section: Pharmacoeconomic Aspe Cts Of Ait Versus Pharmacothe Rapy Fmentioning
confidence: 99%
“…220 ICERs for cost evaluations of AIT seem to vary substantially between different health systems suggesting that straightforward conclusions may not be generalizable even across seemingly similar countries. 215 Finally, the quality of the studies and the general lack of attention to characterizing uncertainty and handling missing data should be taken into account when interpreting these results.…”
Section: Pharmacoeconomic Aspe Cts Of Ait Versus Pharmacothe Rapy Fmentioning
confidence: 99%
“…Other studies addressed SLIT or SCIT as a group 29 or conducted a pharmacoeconomic analysis alongside a clinical trial with placebo as only comparator 34 . Health economic analyses with GRZ and ALD vs placebo were presented in four publications of two health economic studies, one of each treatment 34,[40][41][42] . They concluded that ALD was dominant and GRZ had reasonable cost-utility ratios (e.g., E18,263 in Germany for an annual tablet price of E1500).…”
Section: Discussionmentioning
confidence: 99%
“…Observations from a number of studies with SIT serve as basis for this assumption, showing sustained efficacy for 6 more years after 3 years of treatment [11][12][13][14] . Other cost-effective analyses on grass allergens projected results over the same time horizon 34,42 . The exact duration of sustained effect is still under investigation for SLIT products 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Health economics studies of SCIT conducted outside the United States include findings from prospective clinical trials of AR-diagnosed adults with or without asthma conducted in Italy and the Czech Republic 1,3 ; patient and physician questionnaires obtained from allergy clinics in Denmark and France 4,7 ; and decision-tree and Markov cost-effectiveness models developed in France and Germany based on data derived from systematic literature reviews, Delphi panels, and retrospective claims analyses (Table II). 14,16-18 SCIT has been consistently shown to be cost saving and cost effective, 1,3,7,14,[16][17][18] with the exception of 1 study. 4 This anomalous study had significant disadvantages: (1) data were based on patient recall of health care use for up to 7 previous years; (2) drug use was restricted to allergy or asthma medications and did not include antibiotics or other medications that may serve as clinically meaningful signals of treatment effect; and (3) annual medication use, which was projected from 7 months of actual data that included the peak grass pollen season, may have overestimated actual use of medications.…”
mentioning
confidence: 99%